2018
DOI: 10.1186/s12884-018-1882-2
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and involvement of husbands in maternal and newborn health in rural Bangladesh

Abstract: BackgroundAccess to skilled health services during pregnancy, childbirth and postnatal period for obstetric care is one of the strongest determinants of maternal and newborn health (MNH) outcomes. In many countries, husbands are key decision-makers in households, effectively determining women’s access to health services. We examined husbands’ knowledge and involvement regarding MNH issues in rural Bangladesh, and how their involvement is related to women receiving MNH services from trained providers.MethodsWe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
80
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 42 publications
14
80
4
2
Order By: Relevance
“…39,44 However, involving men in maternal and newborn health care is important and may contribute to facilitating women's access to and utilisation of skilled health services. 52,53 Indeed, WHO recommends implementing interventions to promote the involvement of men in maternal and newborn health. 54 Notwithstanding, it is important to understand the preferences of women pertaining to the involvement of their husbands/male partners specifically at the time of birth.…”
Section: Discussionmentioning
confidence: 99%
“…39,44 However, involving men in maternal and newborn health care is important and may contribute to facilitating women's access to and utilisation of skilled health services. 52,53 Indeed, WHO recommends implementing interventions to promote the involvement of men in maternal and newborn health. 54 Notwithstanding, it is important to understand the preferences of women pertaining to the involvement of their husbands/male partners specifically at the time of birth.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Our findings suggest that although husbands and other family members may be important in the decisions around choosing place of birth in Brahmanbaria, this is not the primary barrier to facility birth and seems to play a lesser role than in some other settings, particularly in Africa. Other studies from Bangladesh have suggested that men play an important role in care seeking for maternal and newborn health services.…”
Section: Discussionmentioning
confidence: 73%
“…Other studies from Bangladesh have suggested that men play an important role in care seeking for maternal and newborn health services. 37,38 Our findings suggest that although husbands and other family members may be important in the decisions around choosing place of birth in Brahmanbaria, this is not the primary barrier to facility birth and seems to play a lesser role than in some other settings, particularly in Africa. 39,40 Programs should include husbands and family members in activities promoting women's empowerment, so that their preferences regarding place of birth are respected and realized.…”
Section: F I G U R Ementioning
confidence: 73%
“…However, few studies to date have examined the preferences of women regarding their husbands'/male partners' involvement in MNH care and how husbands' reported involvement compare to women's preferences, and the decisionmaking dynamics within the household. Bangladesh tends to be characterized by being a patriarchal society in which pregnancy and childbirth are typically relegated to the women's sphere [18,23,36]. However, the results of our study indicate that women in rural Bangladesh would like to enjoy a high level of involvement of their husbands across various areas of MNH care which include assisting in self-care during pregnancy, participating in planning for birth and potential complications, accompanying to health services, and caring for the newborn.…”
Section: Discussionmentioning
confidence: 77%
“…Then measures of association between different explanatory variables were tested through binary logistic regression. The effect of covariates and known confounders were adjusted by multiple logistic regression models for the following factors: age, education, religion, parity, husband's living status, women's involvement in income generating activities, wealth quintile, joint decision-making and women's preferences [36][37][38][39]. All odds ratios (ORs) and adjusted odds ratios (AORs) were reported with 95% confidence intervals (CI).…”
Section: Supporting Women In Self-care During Pregnancymentioning
confidence: 99%